First report on human T-lymphotropic virus 1 infection in a group of transgender women - Carneiro, Megmar Aparecida dos Santos; Margarida, Mykaella Cristina Araújo; Silva, Bruno Vinícius Diniz e; Silva, Ágabo Macedo da Costa e; Matos, Márcia Alves Dias de; Caetano, Karlla Antonieta Amorim; Teles, Sheila Araújo; Vallinoto, Antonio Carlos Rosário; Martins, Regina Maria Bringel (Frontiers in Public Health, 2024)
IntroductionThere is a lack of data on human T-lymphotropic virus 1 (HTLV-1) infection among transgender women (TGW). Therefore, this study estimated the prevalence of HTLV-1 infection in a group of TGW in Brazil.MethodsA cross-sectional study was conducted with 235 TGW in Goiânia City, Central Brazil. Respondent-driven sampling was used for recruitment. All participants were interviewed, and serum samples were tested for anti-HTLV-1/2 using an enzyme-linked immunosorbent assay (ELISA; Murex HTLV-I + II, DiaSorin, Dartford, United Kingdom). Seropositive samples were submitted for confirmation by Western blot (WB; MP Diagnostics HTLV BLOT 2.4 test, MP Biomedicals, Germany).ResultsThe majority of participants were young (≤ 25 years old), self-declared mixed or brown ethnicity, single, had attended high school, and had a monthly income above US$ 255 (R$ 1,000,00; nearly the minimum wage in Brazil at the time). Most reported earlier age at first sex and various risk behaviors for sexually transmitted infections (STIs). Three TGW were anti-HTLV-1/2 positive by ELISA and were subsequently positive for HTLV-1 by WB, giving a crude HTLV-1 seroprevalence of 1.3%; 1.0% (95% CI: 0.0–1.9) after being weighted by RDS Analysis Tool (RDSAT). The HTLV-1 seropositive TGW reported high-risk sexual behaviors. In addition, one of them also engaged in injecting drug use.ConclusionThese data indicate the circulation of HTLV-1 in TGW in Goiânia City, Central Brazil. Given the alarming estimates of high-risk sexual behaviors, there is an urgent need to intensify health programs targeting this population to control and prevent HTLV-1 and other STIs effectively.